Object-oriented and classical software engineering - Schach, Stephen R. (McGraw-Hill Higher Education, 2005)
Object-Oriented and Classical Software Engineering, 6/e is designed for an introductory software engineering course. This book provides an excellent introduction to software engineering fundamentals, covering both traditional and object-oriented techniques.